Effect of diet combined with exercise intervention on tumor necrosis factor α in overweight or obese groups: Based on the exercise dose-response relationship - Chuan qiu shui Wang; Kun Wang; Shi qi Liu; Liang Sun; Jiong Luo (Quality in Sport)
Background: Chronic low-grade systemic inflammation, often linked to obesity or being overweight, is associated with various complications and an increased risk of disease development. Tumor necrosis factor α (TNF-α) is a key inflammatory factor that significantly impacts various body functions.